Perempuan sebagai Simbol dalam Penciptaan Seni Lukis Kontemporer - Ramadhanti, Atiqah Suci; Sami, Yasrul (AHKAM, 2023)
The purpose of the creation of this work is as a work of social criticism and messenger because it visualizes the negative behavior received by women in their social life in society in contemporary painting. The method of creating the work uses five stages, namely the preparation stage (observation and exploration), elaboration (searching and collecting references), synthesis (application of main ideas), realization of concepts (making works) and the completion stage (in the form of reports and exhibitions of final works). In creating the artworks, the author used acrylic paint and mixed media in the form of paper on canvas. The ten works that the author created each contain themes about the struggles and feelings of women amidst the onslaught of negative comments as they try to live a better life, the resulting works measure 100 x 120 cm with titles including: Judge, I Can Fly Too, Aku dan Saya, Kami Tidak Sama, Perempuan! Bukan Wanita, Money Can't Buy Your Freedom, Kehormatan, Jujur, Madame Red, and Tatap.